Preservation of aortic leaflets during rapid deployment valve implantation in patients with aortic insufficiency. Issue 4 (25th February 2019) - Magarakis, Michael; Macias, Alejandro E.; Brozzi, Nicolas; Salerno, Tomas A.
Abstract: Development of a new surgical technique for aortic valve replacement with the use of rapid deployment/sutureless valve: a leaflet preservation technique applying imbrication methods to pliable aortic leaflets. We aim to decrease the incidence of paravalvular leak by preserving aortic leaflets in patients with aortic insufficiency and large aortic annulus.